Optimizing Preanesthesia Care for the Gynecologic Patient. Issue 2 (August 2019) - Dowdy, Sean C.; Kalogera, Eleftheria; Scott, Michael
Abstract : In the past, best practices for perioperative management have been based as much on dogma as science. The creation of optimized perioperative pathways, known as enhanced recovery after surgery, has been shown to simultaneously improve patient outcomes and reduce cost. In this article, we critically review interventions (and omission of interventions) that should be considered by every surgical team to optimize preanesthesia care. This includes patient education, properly managing existing medical comorbidities, optimizing nutrition, and the use of medications before incision that have been shown to reduce surgical stress, opioid requirements, and postoperative complications. Anesthetic techniques, the use of adjunct medications administered after incision, and postoperative management are beyond the scope of this review. When possible, we have relied on randomized trials, meta-analyses, and systematic reviews to support our recommendations. In some instances, we have drawn from the general and colorectal surgery literature if evidence in gynecologic surgery is limited or of poor quality. In particular, hospital systems should aim to adhere to antibiotic and thromboembolic prophylaxis for 100% of patients, the mantra, "nil by mouth after midnight" should be abandoned in favor of adopting a preoperative diet that maintains euvolemia and energy stores to optimize healing, and bowel preparation should be abandoned for patients undergoing gynecologic surgery for benign indications and minimally invasive gynecologic surgery. Abstract : Optimizing preanesthesia care improves outcomes for women undergoing gynecologic surgery.